Guidelines for design solutions for process equipment failures. (Center for Chemical Process Safety of the American Institute of Chemical Engineers, 1998)
While there is no "perfect" solution or absolute zero risk, engineering design can significantly reduce risk potential in the CPI. In Guidelines for Design Solutions to Process Equipment Failures, industry experts offer their broad experience in identifying numerous solutions to the more common process equipment failures including inherent safer/passive, active, and procedural solutions, in decreasing order of robustness and reliability. The book challenges the engineer to identify opportunities for inherent and passive safety features early, and use a risk-based approach to process